Bicycle use planning experiences: global, Latin American and Colombian contexts - QUIJANO MORENO, JEISON SEBASTIAN; QUINTERO GONZÁLEZ, JULIÁN RODRIGO (Uptc, 2024)
The bicycle is one of the most feasible solutions for mobility in cities. Its use brings environmental, social and economic benefits. However, the methods and strategies for its planning are still unknown. The objective is to reflect on the outstanding experiences of planning bicycle use. The methodology consists of the synthesis of the benefits of the cycling mode of transport and its planning process. Based on these two concepts, an exploration of the cases of implementation of bicycle use in cities in the global, Latin American and Colombian contexts is carried out. The planning methods used, infrastructure developments and the management of bicycle use are analyzed. It is concluded that the benefits of bicycle use, as well as the various approaches to its planning successfully implemented, justify the inclusion of infrastructure projects for cyclists in the development plans of territorial governments, and their materialization